Characteristics and treatment strategies of the hip fracture triad - Li, Lin; Li, Lianxin; Zhou, Dongsheng; Zhao, Qin; Li, Ci (Frontiers in Surgery, 2025)
ObjectiveTo explore the clinical characteristics and treatment strategies of the hip fracture triad (acetabular fracture, hip dislocation combined with proximal femur fracture).MethodsA retrospective analysis was performed on 11 patients with hip fracture triad admitted to Shandong Provincial Hospital from January 2014 to December 2020. There were 9 males and 2 females; age (38.7 ± 12.2) years old (range 12–53 years). After all patients are admitted to the hospital, a treatment plan will be formulated based on the fracture type and associated injuries, and long-term follow-up will be conducted.ResultsThis study included clinical data of 11 patients with hip fracture triad, of which 9 cases were treated surgically and 2 cases were treated conservatively. All patients were followed up. 9 patients successfully completed the operation. The operation time was (4.4 ± 1.4) hours (range 3–8 h); intraoperative bleeding was (600.0 ± 355.9) ml (range 400–1,200 ml). Fracture reduction was evaluated according to the acetabular fracture Matta score: 7 cases were excellent, 2 was good, and none was poor; 2 patients with old injuries chose conservative treatment as the final treatment plan. Acetabular fractures at the final follow-up were evaluated using the modified Merle d'Aubigné-Postel score of the hip joint: 7 cases were excellent, 1 was good, and 3 were poor. 1 patient developed traumatic hip arthritis after surgery, underwent total hip arthroplasty, and recovered well after surgery; 1 patient underwent hemihip arthroplasty 1 year after surgery due to femoral neck fracture and recovered well after surgery; 1 patient suffered from cerebral infarction complicated by long-term bed rest, poor hip joint mobility and basic loss of self-care ability; 2 patients with conservative treatment of old fracture had limited hip joint functional mobility, unequal length of both lower limbs, and poor hip joint mobility.ConclusionThe hip fracture triad is a complex, high-energy injury that is extremely rare clinically. A correct understanding of the characteristics and mechanism of this type of injury, and prompt and effective treatment strategies, will help improve patient prognosis. Surgery is the preferred treatment option for this injury, and early reduction or lower limb traction can help reduce the occurrence of postoperative complications.